CAUSALITY ANALYSIS BETWEEN INFLATION, JUB, SBIS, PUAS AND SBSN USING COINTEGRATION AND GRANGER CAUSALITY APPROACH - Zainal Arifin Siregar; M. Ridwan; Maryam Batubara (ITB AAS INDONESIA, 2023)
Inflation , the Money Supply (JUB) has been widely discussed and researched by previous researchers, the results from previous studies indicate a gap from the results of each research, in this study the researchers added the variable Bank Indonesia Sharia Certificate (SBIS) , Sharia Interbank Money Market (PUAS) and State Sharia Securities (SBSN) as sharia monetary policy which is also related to the variables of Inflation and the Money Supply (JUB) . The purpose of this study is to determine the long and short-term relationship between variables as well as to determine the direction of the relationship between variables. This research is a quantitative study, using secondary data based on monthly data from 2015 to 2020. The analysis used in this study uses cointegration analysis (long-term relationship) and Granger causality (direction of relationship between variables). The results of this study indicate that in the long term inflation has a positive and significant effect on the JUB variable and a negative and significant effect on the SBIS and SBSN variables while the PUAS variable has an insignificant effect. In the short term, inflation in the previous period had a negative and significant effect on current inflation, SBIS and SBSN while JUB and PUAS had an insignificant and insignificant effect. The previous JUB had a negative and significant effect on the current JUB, SBIS and SBSN variables, while the inflation variable had a positive and significant effect, while the PUAS variable had an insignificant effect. PUAS in the previous period had a negative and significant effect on the current PUAS and SBSN variables, while the Inflation, JUB and SBIS variables had no significant effect. The previous period SBIS had a negative and significant effect on the inflation and JUB variables, while the PUAS, current SBIS and SBSN variables had no significant effect. The previous period SBSN had a negative and significant effect on the inflation variable, current JUB and SBSN, while the PUAS and SBIS variables had no significant effect. In the Granger causality test there is a unidirectional relationship between SBIS and inflation, there is a unidirectional relationship between inflation and SBSN, there is a unidirectional relationship between JUB and PUAS, there is a unidirectional relationship between JUB and SBSN, PUAS and SBIS have a two-way relationship, SBSN has a unidirectional relationship with PUAS and SBSN have a unidirectional relationship with SBIS.